Portuguese ecotypes of Opuntia ficus-indica differ in biomass production - gazarini, l.c. (2015)
The Opuntia ficus-indica (L.) Miller is a species from the Cactaceae family with the center of origin and domestication in central Mexico. This species introduction in the Iberia Peninsula occurred, probably, by the end of the 15th century, after the discovery of America, spreading later throughout the Mediterranean basin. In Portugal, O. ficus-indica is located, usually, with a typical ruderal behavior, at the edge of roads and paths. In Portugal, as in other Mediterranean regions, inlands areas are under severe draught during extensive summers, in particular, and global warming is expected to affect them deeply in the near future. O. ficus-indica, by its morpho-physiological characteristics and multiple economic uses, represent an alternative crop for those regions. Sixteen Portuguese O. ficus indica ecotypes and two ‘Italian’ cultivars ("Gialla" and "Bianca") were evaluated for plant vigor and biomass production, by nondestructive methods, in the two years following planting. Biomass production and plant vigor were measured by estimating cladode number, cladode area and fresh weight per plant. Linear models to predict the area of cladodes and fresh weight per plant were previously established using a biometric analysis of 180 cladodes. It was not possible to establish an accurate linear model for dry matter using non-destructive estimation. Significant differences were found among populations in the studied biomass-related parameters, and different groups were unfolded. A group of four Portuguese ecotypes outperformed in terms of biomass production, comparable with the “Gialla” cultivar. This group could be used to start a breeding program with the objective of deploy material for animal feeding, biomass and fruit production. Nevertheless, the ‘Gialla’ cultivar showed the best performance, achieving the highest biomass related parameters, not surprisingly for it is an improved plant material.